Formation of Religious Character through the Al-Quran Tahfidz Programme at Ad-Dirosat Al-Quraniyah Islamic Boarding School in Bajur Waru Pamekasan - Faruq, Umarul (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
This research seeks to comprehensively examine the efforts to internalise religious values at the Ad-Dirosat Al-Quraniyah Islamic Boarding School in Bajur Waru Pamekasan.